Synthesis, Characterization and Biological Activity Study of New Compounds Tetrazole Derivatives Azo-Schiff Base (Journal of the College of Basic Education, 2019)
This work included synthesis of azo dye (H1) by the reaction of diazonium salt to sulfacetamide with 4-hydroxy benzaldehyde at (0-5) oC and synthesis of schiff base (H2-H6) through reaction substituted aromatic amine (aniline, 4-nitro aniline, 4-chloro aniline, 4-amino benzoic acid and phenyl hydrazine) with aldehyde group in azo compound (H1) in ethanol compounds (H2-H6) and tetrazole derivatives prepared by reaction schiff base with sodium azide in ethanol compounds (H7-H11) and characterization by using spectroscopic techniques Uv/Vis, FT-IR, C.H.N. and H1-NMR of some the prepared compounds using DMSO-d6 a solvent, in addition melting point and determination a purity of TLC, and this work consists a study of biological activity for the some prepared compounds against four types of pathogenic bacteria and know to be resistant to anti biotic.